2007
DOI: 10.1080/15374410701444306
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Adjustment of African American Youth from Single Mother Homes: The Relative Contribution of Parents and Peers

Abstract: This study examined the relative roles of parents and peers in the psychosocial adjustment of African American youth (7-15 years old) from single mother homes (N = 242). Main effects of both positive parenting and peer relationship quality were found for youth depressive symptoms. In addition, a main effect of peer relationship quality and an interaction of Positive Parenting x Peer Relationship Quality emerged for youth externalizing symptoms. When mothers engaged in higher levels of positive parenting behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 48 publications
(59 reference statements)
2
46
1
1
Order By: Relevance
“…Our findings regarding the lack of any influence of close peer relationships on mental health problems for our entire sample are in conflict with results from a number of studies that showed a significant relationship between poor quality of peer relationships and depression, social anxiety, and internalizing problems (Bosacki et al, 2007;Chester et al, 2007;Cho & Bae, 2005;McDonald et al, 2010;Mendle et al, 2012). However, our findings are consistent with results from 2 studies showing that the quality of close friendships was not a significant factor in delinquency (Selfhout et al, 2008) or in the development of overall mental health problems (Okello, Nakimuli-Mpungu, Musisi, Broekaert, & Derluyn, 2014).…”
Section: Friendship Quality and Mental Healthcontrasting
confidence: 56%
See 1 more Smart Citation
“…Our findings regarding the lack of any influence of close peer relationships on mental health problems for our entire sample are in conflict with results from a number of studies that showed a significant relationship between poor quality of peer relationships and depression, social anxiety, and internalizing problems (Bosacki et al, 2007;Chester et al, 2007;Cho & Bae, 2005;McDonald et al, 2010;Mendle et al, 2012). However, our findings are consistent with results from 2 studies showing that the quality of close friendships was not a significant factor in delinquency (Selfhout et al, 2008) or in the development of overall mental health problems (Okello, Nakimuli-Mpungu, Musisi, Broekaert, & Derluyn, 2014).…”
Section: Friendship Quality and Mental Healthcontrasting
confidence: 56%
“…Chester, Jones, Zalot, and Sterrett (2007) found that African American youth who had better quality in their peer relationships had lower levels of depressive symptoms, less aggression, and fewer delinquent behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A general review of the literature indicates that a belief in others is positively related to psychological well-being (Resnick et al 1997;Jose et al 2012). In particular, increased peer support in adolescence has been found to predict lower levels of depression in cross-sectional and longitudinal studies (Allen et al 2006;Chester et al 2007). School support and school connectedness are linked to a number of positive youth outcomes including increased self-esteem, self-efficacy, optimism, and positive peer relationships (Osterman 2000;Resnick et al 1997) and are negatively related to depression, anxiety, emotional distress, suicidality, and the development of conduct problems in adolescence (Loukas et al 2010;Shochet et al 2006).…”
Section: Belief In Othersmentioning
confidence: 96%
“…Additionally, the associations involving scholastic achievement among Hispanic and African American youth were unexpected, since this exacerbated depression when exposed to cumulative risk (Chester et al 2007;Resnick et al 1997). Luthar and McMahon (1996) note that when there are opposing values between one's peer group and those of larger society, scholastic-minded minority youth may be pressured by peers to conform to group standards.…”
Section: Protective Mechanismsmentioning
confidence: 99%